The Nexus between Mobile Game Usage and Student Academic Performance of Management Students at the University Level in Kathmandu - Luitel, Peshal; Neupane, Bharat Prasad (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
This study examines the relationship between online gaming frequency and academic performance among university-level students in Kathmandu Valley. With the growing use of mobile phones and digital technology, students increasingly socialize through online platforms, including mobile games. Using a descriptive and causal research design, data were collected from 300 MBA, BBA, and BBS students through a purposive sampling technique and analyzed using statistical tools like correlation and regression. The findings reveal that while the impact of online gaming frequency on academic performance is minor, it varies by gender. The study recommends awareness programs for students, parents, and teachers to understand the positive and negative impacts of online gaming. Teachers are encouraged to incorporate educational games to enhance critical thinking and analytical skills. Future research should explore additional factors affecting academic performance with a larger, more diverse sample size for deeper insights.